Razvijanje računalniškega mišljenja pri učencih 2. razreda - Weis, Klementina (Revija inovativna pedagogika, 2025)
The paper presents a good practice example of basic computational thinking development and introduces the concepts of repetition (loops) and decision-making with simple decision-making structures. The conducted activities consisted of three themes. We revised and strengthened basic computational thinking concepts with the aid of mTiny robots and coding cards. After that, we introduced the loop concept. Our third theme was coding with decision trees. We wanted to determine whether these various concepts interfere with each other in activities that demand understanding and solving given tasks. With the research, we tried to develop pupils’ logical thinking and creativity, collaboration skills, and ability to divide complex problems into minor ones. For the chosen area of computing and informatics, algorithms, and coding, the data was collected by participant observation. The chosen method showed that cases of executed activities were effective. The mentioned concepts are complementary. The pupils progressed in breaking down problems, logical thinking, creativity, collaboration, and communication. Provided feedback consisted of approval, constructive criticism, and encouragement to listen to each other and learn from their fellow peers' experiences.
Keywords: algorithms and coding; algoritmi in programiranje; computational thinking; decision-making (branching); Informacijsko-komunikacijska tehnologija; odločanje (vejitev); Osnovnošolsko izobraževanje; ponavljanje (zanke); računalniško mišljenje; repetition (loops)